Mule Deer Habitat Selection Following Vegetation Thinning Treatments in New Mexico - Grant E. Sorensen; David W. Kramer; James W. Cain III; Chase A. Taylor; Philip S. Gipson; Mark C. Wallace; Robert D. Cox; Warren B. Ballard (Wildlife Society Bulletin)
ABSTRACT Mule deer (Odocoileus hemionus) survival and population growth in north‐central New Mexico, USA, was previously reported to be limited by nutritional constraints due to poor forage conditions in degraded habitats. Management recommendations suggested thinning of pinyon–juniper to improve habitat quality for mule deer. To evaluate the influence of these vegetation treatments, we monitored habitat selection by 48 adult female mule deer from 2011 to 2013 in a population previously reported to be nutritionally limited. Monitoring occurred 1–4 years after completion of treatments that were intended to improve forage conditions, including mechanical reduction of pinyon pine (Pinus edulis) and juniper (Juniperus spp.) density and senescent brush (Quercus gambelii–Cercocarpus montanus) cover. During the summer season, deer selected recently treated areas, but odds ratios decreased with treatment age. However, during winter, deer avoided more recently treated areas and selected thinned areas >4 years old. Deer selected mixed oak (Quercus spp.) and pinyon–juniper savanna vegetation cover types with a moderately open canopy and ponderosa pine (Pinus ponderosa) forests while avoiding grasslands and montane shrublands across all seasons. Deer selected areas closer to water and developed areas, northeast aspects, on gentle slopes, and at lower elevations. Creating a savanna‐like cover type may elicit a positive deer response as a result of their strong avoidance of dense, closed canopy pinyon–juniper woodlands. © 2020 The Wildlife Society.